Start-up and performance of a downflow fluidised bed reactor for biological treatment of yellow wastewater and nutrient recovery - Belem Espinosa-Chávez; Florina Ramírez-Vives; Grietje Zeeman; Oscar Monroy-Hermosillo (Water Science and Technology, 2022)
The treatment of yellow water (human urine) in a downflow fluidised bed reactor (DFFBR) was investigated to evaluate biological ureolysis and nutrient recovery. The reactor was operated at 30±4 °C in batch mode, and reaction time = 1 d. The average immobilised biomass (as volatile solids, IVS) in the reactor was 2.5±0.9 g L−1support, and specific ureolytic activity was 121 g Urea-N g−1 IVS d−1. The kinetic parameters were 0.152 mol L−1 (Km) and 8 mol g−1 IVS d−1 (Vmax). The ureolysis efficiency was 93.4% and chemical oxygen demand removal efficiency was 31.2%, while total ammonium nitrogen (NH4+-N) production rate was 7 g L−1 d−1 and phosphate removal reached 26%. Precipitates recovery during biological treatment was 1.72±0.8 g. These results suggest that the treatment of yellow water in a DFFBR is a viable option for partial recovery of N and P. HIGHLIGHTS A new biological treatment of yellow water is proposed.; Yellow waters were treated effectively in a downflow fluidised bed reactor.; The biological ureolysis of human urine was reached within six hours.; After addition of Mg2+/PO43− (1.6/1), 82.3 g of precipitates were recovered.; Struvite was the major component of the recovered precipitates.;